‘What to cook and how to cook it’: Understanding the interplay of subsistence, ceramic technology, and local environments in the emergence of pottery in northeast Asia through residues - Keute, J (2022)
Since the early 2000’s, archaeological excavations in the Nenjiang River Basin have led to the discovery of some of the oldest pottery assemblages in northeast China. The main objective of the DPhil research presented here is to understand what role vessel technology played in human lives over an extended time span regarding diets, food preferences, and human environmental interactions in this region. Pottery analysed in this thesis comes from the site of Houtaomuga 后套木嘎 located in the Lower Nen River Valley on the Song-Nen Plain, Jilin province northeast China. Using molecular and isotopic analysis, this thesis characterised lipids extracted from archaeological pottery using advanced analytical methodologies to understand pottery use at the initial implementation of the technology and over the course of the Neolithic. Results of lipid residue analysis presented as a part of this research were also described in context with other regions in northeast Asia, such as Russia’s Far East and Japan, which also have pottery bearing hunter-gather sites from the Neolithic which are contemporaneous.